Correlation of arbuscular mycorrhizal dosage with level of colonization, nutrient concentration, and photosynthesis pigment of Cavendish banana plant - Akib, Muhammad Akhsan; Ilmi, Nur; Risnawati, Risnawati; Prayudyaningsih, Retno; Syatrawati, Syatrawati (Universitas Padjadjaran, 2024)
The commercial development of Cavendish bananas still faces many obstacles, including the availability of seedlings/suckers at low prices, so technological substitution is needed to stimulate the growth of Cavendish banana suckers in the form of arbuscular mycorrhizal (AM) biological agents. The research aims to determine the correlation between AM doses and colonization levels, tissue nutrient concentrations, and photosynthetic pigments in Cavendish banana seedlings/suckers. It is also a novelty in this research study. The research was carried out in Parepare city at coordinates 3°59'30.204